Penerapan Teori Kognitif Sosial Dan Implikasinya Dalam Pembelajaran PAI - Hendro Perdana Putra; Ahmad; Muhammad Arif Pahsa Al Muttaqin; Irvan; Husni Idris (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the application of social cognitive theory and its implications for Islamic Education (PAI) learning. The theory emphasizes that learning occurs through reciprocal interactions among personal, behavioral, and environmental factors. In PAI, it is relevant as it positions students as active learners who develop understanding through observational learning, modeling, reinforcement, and self- efficacy. This research employs a literature review method, analyzing relevant works on social cognitive theory and PAI practices. The findings indicate that applying this theory enhances learning motivation, deepens understanding of Islamic values, supports character development, and strengthens students’ ability to internalize religious teachings in daily life. Practical implications highlight the importance of teachers as role models, the use of contextual and collaborative learning approaches, and the creation of supportive learning environments. Overall, social cognitive theory contributes significantly to improving PAI learning quality, making it more effective, meaningful, and oriented toward character formation.